2013
DOI: 10.1016/j.bcab.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

13C and 15N partitioning among shoots, roots, and soil in Brassica napus genotypes varying in seed oil content potential

Abstract: N partitioning among shoots, roots, and soil in Brassica napus genotypes varying in seed oil content potential, Biocatalysis and Agricultural Biotechnology, http://dx.doi.org/ 10. 1016/j.bcab.2013.02.001 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The study of Fei et al (2013) indicated an inverse relationship between seed oil content potential on the one hand, and biomass, C, and N accumulation on the other. Hence, the partition of mobilized C and N from vegetative biomass to seeds seems to determine the realized seed oil content much more.…”
Section: Defining the Ideotype Of A Nitrogen-efficient Rapeseedmentioning
confidence: 96%
“…The study of Fei et al (2013) indicated an inverse relationship between seed oil content potential on the one hand, and biomass, C, and N accumulation on the other. Hence, the partition of mobilized C and N from vegetative biomass to seeds seems to determine the realized seed oil content much more.…”
Section: Defining the Ideotype Of A Nitrogen-efficient Rapeseedmentioning
confidence: 96%
“…Plants of the two mutant genetic lines and their WT parents were labeled with 13 CO 2 at growth stage 6.5 in a custom-designed labeling chamber (Fei et al 2013) During labeling, the PPFD was 300 mol·m −2 ·s −1 , the temperature ranged approximately between 24 and 28°C, the relative humidity ranged between 90% and 95%, and the atmospheric CO 2 concentration was monitored by a CO 2 gas analyzer (LiCor-820; LI-COR Biosciences, Lincoln, Nebraska, USA).…”
Section: Labelingmentioning
confidence: 99%
“…Cultivars, experimental lines, and generated double-haploid lines of B. napus indicated that C and N partitioning were affected by seed oil productivity (Fei et al 2013). Four genotypes of B. napus (cultivars Topas, Sentry and Polo, and the experimental line 04C204) varying in SOC potential from 42 to 50% seed dry weight were used to study C and N partitioning among shoots, roots and soil, as well as nitrogen use efficiency.…”
Section: General Findings and Relationship Withmentioning
confidence: 99%